The impact of generalized floating on trade flows and reserve needs : selected Asian developing countries - Rana, Pradumna Bickram (New York : Garland Pub., 1983)
The dissertation focuses on the validity of the first two sets of complaints. To begin with, since Cline's study did not find any trade-diverting bias, the dissertation attempts to examine the anti-trade bias of the present system. it was not possible to study the effect of exchange risk on capital flows because of the unavailability and unreliability of data. With regard to the second set of problems, the dissertation seeks to study the reserve needs of LDCs under the present system. The dissertation is organized in the form of four essays which are basically independent of each other.
Originally presented as the author's thesis (Ph.D.--Vanderbilt University, 1979)
Includes bibliographical references: p. 216-227.
rpm 27/03/2018
Loans
Keywords: Foreign exchange rates; Foreign exchange; Developing countries